Government Interventions on Tobacco Control in India: A Critical Review. Issue 2 (August 2019) - Mukherjee, Sanchita; Mishra, U. S.
Tobacco use is a serious concern in India since it is one of the largest producers and consumers of tobacco in the world. With growing evidence of health hazards caused by tobacco, Government of India had enacted various tobacco control legislations. This article provides a critical review of such government interventions. It traces tobacco practices and production trends in India, and proceeds further to provide a detailed account of the history of such interventions to understand the effectiveness of such policies, and stresses on the role of tobacco companies to weaken tobacco control policies in India. This article concludes that though tobacco control has taken a long leap forward with the introduction of various legislative steps to prohibit tobacco use across the country, review of these policies shows their inadequacy not only in enforcement but also in issues related to (a) the interference of the tobacco industry, (b) issues with tobacco taxation and (c) the failure of government to rehabilitate people involved with cultivation, production and distribution of tobacco products.